EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) BERBANTUAN WINPLOT DAN TEAM ASSISTED INDIVIDUALIZATION (TAI) PADA MATERI APLIKASI TURUNAN FUNGSI DITINJAU DARI KEMAMPUAN PENALARAN MATEMATIS SISWA - Wawan, Wawan; Mardiyana, Mardiyana; Iswahyudi, Gatut (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2014)
Abstract: The objective of this research was to investigate the effect of the learning models on the learning achievement in mathematics viewed from the reasoning abilities of the students. The models compared were the cooperative learning model of the Winplot-assisted STAD, the cooperative learning model of the TAI type, and the Powerpoint-assisted direct learning model. This research used the quasi experimental research method with the factorial design of 3 × 3. Its population was all of the students in grade XI of Senior Secondary Schools of Purworejo in academic year 2013/2014. The samples of the research were taken by using the stratified cluster random sampling technique. The size of the sample was 235 students consisted of 80 students in the first experimental class, 77 students in the second experimental class and 78 students in the control class. The instruments to gather the data of the research were test of learning achievement in mathematics and test of mathematical reasoning ability. The data was analyzed by using the two-way analysis of variance with unbalanced cells. The conclusions of this research were as follows. (1) The cooperative learning model of the Winplot-assisted STAD type resulted in a better learning achievement in mathematics than the cooperative learning model of the TAI type and the Powerpoint-assisted direct learning model, and the cooperative learning model of the TAI type resulted in a better learning achievement in mathematics than the Powerpoint-assisted direct learning model. (2) The students with the high mathematical reasoning ability had a better learning achievement in mathematics than those with the moderate and low mathematical reasoning abilities, and the students with the moderate mathematical reasoning ability had a better learning achievement in mathematics than those with the low mathematical reasoning ability. (3) In each mathematical reasoning ability category, the cooperative learning model of the Winplot-assisted STAD type resulted in a better learning achievement in mathematics than the cooperative learning model of the TAI type and the Powerpoint-assisted direct learning model, and the cooperative learning model of the TAI type resulted in a better learning achievement in mathematics than the Powerpoint-assisted direct learning model. (4) In each learning model, the students with the high mathematical reasoning ability had a better learning achievement in mathematics than those with the moderate and low mathematical reasoning abilities, and the students with the moderate mathematical reasoning ability had a better learning achievement in mathematics than those with the low mathematical reasoning ability.Keywords: STAD, Winplot, TAI, direct learning, mathematical reasoning, and learning achievement in mathematics.